Analisis Tingkat Partisipasi Masyarakat Dalam Pengembangan Ekowisata di Kecamatan Petungkriyono, Kabupaten Pekalongan - Muhammad Nahrowi (Universitas Sebelas Maret (UNS), 2022)
This research was conducted in Petungkriyono District, Pekalongan Regency in 2019. Petungkriyono District is an area in Pekalongan Regency that is designated as an ecotourism area and protected forest. The purpose of this research is to analyze the level of community participation in the development of ecotourism in Petungkriyono District, Pekalongan Regency. This study used descriptive qualitative method. The data collection techniques used were observation, interview, and documentation. The data obtained using the analysis of participation according to Arstein's ladder of participation, then classified into 3 (three) levels of community participation. The results showed the level of community participation in the development of ecotourism in Petungkriyono District, there were 3 (three) levels of participation, namely (1) high level of participation (citizen power); (2) moderate level of participation (tokeism); and a low level of participation (non-participation). Keywords : participation level, ecotourism development